Perancangan Aplikasi Chat Graphical User Interface (GUI) Antar Client dengan Bantuan Java Socket Untuk Mahasiswa Jurusan Teknik Elektro Universitas Riau - Putra, Candra Galang Gemilang; Ramadhani Muliaqalbi, Putri; Pahlevi, Reza; Ayu Nabila, Rina; Madihah Syahnevi, Salwa; Oktaviana Sari, Linna (Jurnal Ilmiah Wahana Pendidikan, 2024)
Advances in communication technology have driven the development of network-based applications to meet the need for efficient and effective communication. Chat applications have become one of the most popular solutions to provide an interactive platform that enables the exchange of information quickly and easily. The development of information technology today has changed the paradigm of interaction between individuals, especially in the world of education. Students of the Electrical Engineering Department at Riau University are increasingly facing challenges in developing network-based applications to support academic activities and communication between fellow students. This research aims to design an application with a chat-based Graphical User Interface (GUI), which facilitates communication between students through the use of Java Socket. The use of Graphical User Interface (GUI) in chat applications also provides advantages in terms of user experience, making interaction between users more intuitive and interesting. Therefore, the author proposes a journal design of a GUI-based chat application between clients with the help of Java socket for students majoring in electrical engineering at Riau University.